Requirement for vacuolar proton-ATPase activity during entry of influenza virus into cells. - Guinea, R (1995)
The role that endosomal acidification plays during influenza virus entry into MDCK cells has been analyzed by using the macrolide antibiotics bafilomycin A1 and concanamycin A as selective inhibitors of vacuolar proton-ATPase (v-[H+]ATPase), the enzyme responsible for the acidification of endosomes. Bafilomycin A1 and concanamycin A, present at the low concentrations of 5 x 10(-7) and 5 x 10(-9) M, respectively, prevented the entry of influenza virus into cells when added during the first minutes of infection. Attachment of virion particles to the cell surface was not the target for the action of bafilomycin A1. N,N'-Dicyclohexylcarbodiimide, a nonspecific inhibitor of proton-ATPases, also blocked virus entry, whereas elaiophylin, an inhibitor of the plasma-proton ATPase, had no effect. The inhibitory actions of bafilomycin A1 and concanamycin A were tested in culture medium at different pHs. Both antibiotics powerfully prevented influenza virus infection when the virus was added under low-pH conditions. This inhibition was reduced if the virus was bound to cells at 4 degrees C prior to the addition of warm low-pH medium. Moreover, incubation of cells at acidic pH potently blocked influenza virus infection, even in the absence of antibiotics. These results indicate that a pH gradient, rather than low pH, is necessary for efficient entry of influenza virus into cells.